Efektivitas Analisis Beban Kerja Berbasis Aplikasi (E-ABK) terhadap Penentuan Pemenuhan Kebutuhan Pegawai di Kecamatan Benowo - Shafiya, Nandina Putri; Widiyarta, Agus (IAI Nasional Laa Roiba Bogor, 2024)
The Workload Analysis Application or e-ABK is an electronic-based application that is used to measure and calculate the workload for each position/work unit and obtain information regarding the level of effectiveness and work efficiency of regional apparatus based on work volume. One of the objectives of carrying out this workload analysis is to determine the needs of employees who occupy a position. Based on research in the field, there are still discrepancies between the results of the job analysis, there are discrepancies with the results of the job analysis that have been previously formulated by the Organizational Section which is different from its implementation in the field, namely that not all of the job analysis job descriptions are carried out by office holders in the Benowo sub-district. So this has caused several employees in the Benowo sub-district to complain that employee needs are still not appropriate. This research uses a descriptive research method with a qualitative approach. This research was conducted to determine the effectiveness of Application-based Workload Analysis in determining employee needs in Benowo sub-district. Based on the research results, the use of the Workload Analysis Application (ABK) to determine employee needs based on the effectiveness sub focus of Duncan's theory (1985) can be said to be effective. This is because the 3 focuses have been fulfilled (Goal Achievement, Integrity and Adaptation).